An Experimental Study on Relationship between Performance and Energy Consumption of Serial and Parallel Text Searching Algorithm. - Isahak, Siti Zulaikha (Universiti Teknologi Petronas, 2013)
The world data is growing vigorously intersecting of large ordered sets and it is a common problem in the evaluation of data queries to a search engine. Thus, text retrieval systems have become a popular way in providing support for text databases. However this becomes a major question among us like how much energy is consumed? How to reduce execution time in searching large amount of data? In this paper, text searching algorithm is using to study the relationship between performance of computer and amount of energy produced in serial and parallel text searching algorithm. The amount of energy produced should be reduced along with the execution time to increase performance in data searching. Based on data recorded from the series of experiments, Serial Text Searching Algorithm is saving energy and reducing power usage. However, their performance is reducing as a smaller processor speed is using. In contrast to Parallel Text Searching Algorithm, there are larger amount of energy consumed from this experiment. However, it is approved that the performance of parallel experiment is far better than a single node performance.